Using Mobile Computing to Enhance Skiing An investigation into how mobile computing can be used to enhance the skiing experience - DALEMAR, GUSTAF (My University, 2013)
Skiing is a popular activity in Sweden and about 24% of the population between the age 0 and 74 ski each year. Of these skiers 42% are between the ages of 15 to 45 and around 75% of them have a smartphone. Smartphones are becoming more popular each day and represents the majority of the mobile phone market. With the increase in smartphone usage along with the interest in winter sports, there exist a general interest in how these can be combined, both to benefit the skiers and also the resorts as a way to engage more people into skiing. The aim of this report was to investigate how smartphones can be used to enhance the downhill skiing experience, especially looking into if and how sound can be used as a design parameter. The presented ideas and concepts have been acquired by using established methods to both understand the potential users and evaluate prototypes based on some of the ideas. The report will go trough the process behind the achieved results outlining what has been done in each step of the way. Some of the presented ideas are: a functionality to know where people that you ski with are, an audio feedback system that informs the user about their performance and an algorithm that can be used to detect if a user is in a slope or a lift. Additionally, a new way to interact with a mobile device is presented that do not require the user to take the device out of the pocket.
Keywords: Interaktionsteknik; Interaction Technologies